Pengetahuan, sikap dan praktis kebersihan oral dalam kalangan pelajar sekolah rendah dl daerah Kota Bharu, Kelantan - Jusoh, Wan Nur Azwani Wan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2008)
The increasing of awareness of self-appearance make the oral care was one of the important parts of overall health status. The awareness of oral care should be manure as early as possible among the school students. The knowledge, attitude changes and the practices of oral care must start at home, at school, at hospital or everywhere as the awareness of oral care among school students is still in moderate level. The aim of these studies is to evaluate the level of knowledge, attitudes, and practices of oral care among schoolchildren as well as to identify the factors that determine these variables. These cross-sectional study was involved by two hundred and thirty two (n = 232) of primary school students year one which were chosen from the list of the school which participated in the dental service in the area of Kota Bharu, Kelantan. This study is conducted in two schools in Kota Bharu, Kelantan, including Sekolah Kebangsaan Ismail Petra 1, and Sekolah Kebangsaan Kubang Kerian 3. The researcher used self-administered questionnaire as the instrument. The respondent answered the questionnaire by the help of the researcher. The result from the Chi-Square test shows that there was a statistically significant difference in the level of knowledge on practicing of oral care among primary school students. The mean score and standard deviation of the level of knowledge on practicing of oral care among primary school students was 1.69 (SO = 0.46). The a-value is 0.019 where p < a (0.05) shows that null hypothesis is rejected in the study. The result from the study shows that the level of knowledge among primary school students was in moderate level in practicing of oral care. The test of Chi-Square on attitudes also showed that the p value < a (0.05) which was 0.000. The result shows that there was a statistically significant difference of attitudes on practicing of oral care among primary school students. The mean score and standard deviation of attitude was 2.30 (SD = 0.460). According to the result, the attitude was neutral and it influenced the good practicing of oral care among primary school students. As a conclusion, the finding of this study will be the first step to improve the practice of oral care among primary school students in the future. The teaching of health education in school curriculum and the implementation of school-programmed need to be attention by the Ministry of Health. Thus, the schools, the Ministry of Health, government and non-government should give more attention focusing on the important of oral care among primary school students.